Revisiting Health in Colonial Bengal: A Literary Overview (1880 -1930) - Bhattacharya, Tinni Goswami (Mediterranean Journal of Social Sciences, 2012)
The essential theme of this paper is to highlight the condition of health and hygiene in the British Bengalfrom the perspective of official documents and vernacular writings, with special emphasis on the journalsand periodicals. The fatal effects of the epidemics like malaria and cholera, the insanitary condition of therural Bengal and the cultivated indifference of the British Raj made the lives of the poor natives miserableand ailing.The authorities had a tendency to blame the colonized for their illiteracy and callousness whichbecame instrumental for the outbreak of the epidemics. On the other, in the late 19th and the beginning ofthe 20th, the vernacular literature played the role of a catalyst in awakening health awareness, highlightingthe issues related with ill-health, insanitation and malnourishment. More importantly, it became an activelink between the society and culture on the one hand, and health and people on the other. The presentresearcher wants to highlight these opposite trajectories of mentalities with a different connotation. Theideologies of the Raj and the native political aspirations often reflected in the colonial writings, where theyear 1880 was considered as a landmark in the field of public health policies. On the other, the dichotomybetween the masters and the colonized took a prominent shape during 1930s.Within these fifty years; thehealth of the natives witnessed many upheavals grounded on the social, economic and cultural tensions.